Graphene Based Membranes and Their Application in Gas Separation - Abolhasan Nezhad, Fatemeh (Curtin University, 2020)
Membrane separation technology is one of the most cost-effective methods for gas separation which can be a promising replacement for these conventional methods like cryogenic distillation. Among various types of membranes, molecular sieving membranes (MSMs) are well-known for their high stability and great performance. In this study, a facile method was introduced for fabricating a type of MSM using graphene. The resultant membranes exhibit excellent gas separation performance with considerably high permeance and selectivity.